Studi Sistem Akustik pada Gereja Katolik Santa Maria Tak Bercela Surabaya - Hedy C. Indrani, Lisayana (Intra, 2013)
The church is a building that has an image of Gods glory so that through space design elements, sacred atmosphere can formone through acoustics. The church has an unique acoustic because the church has two activities, namely speech and music. Santa Maria Tak Bercela Catholic Church Surabaya adjacent to Santa Clara School Surabaya, which at certain hours of the atmosphere will be very crowded church. With the help of Sound Level Meter, the background noise is known and the power of the sound source at this church. Reverberation time is calculated by manually sabine and computerize using program Autodeks Ecotect Analysis 2011. Having in mindthe results of the calculation of reverberation time in the field was 0.79-0.88 seconds, the church should be optimized with the goal of achieving the optimum reverberation time is 1. 4 seconds and the sound proofing leaks, by using materials such as insulation yumen board, glasswoll, acrylic, curtains, glass in sealant, rubber on the doors and closing the door hole.